Wyoming - Prentzas, G. S (New York Children's Press, 2010)
Takes readers on a tour of Wyoming, describing the state's history, culture, land, economy, government, and sights, and including unique facts, color maps and photos, the state song, suggested activities, lists of famous people, cultural institutions, and annual events, and other resources
Land -- First people -- Exploration and settlement -- Growth and change -- More modern times -- People -- Government -- Economy -- Travel guide -- Project room. Projects ; Timeline ; Glossary ; Fast facts ; Biographical dictionary ; Resources ; Index ; Author's tips and source notes
Includes bibliographical references and index
Hurg
5
Keywords: Wyoming -- Juvenile literature; Wyoming